Tourist Attractions Halal Facilities and Satisfaction Drive Revisit Intention: Daya Tarik Wisata Fasilitas Halal dan Kepuasan Mendorong Minat Kunjungan Ulang - Zahroh, Mahdinatul Fitri; Rohman, Wahibur (Universitas Muhammadiyah Sidoarjo, 2026)
This study examines revisit intention in a local tourism destination through key experiential and service-related factors. General Background: Tourism development increasingly emphasizes visitor experience and service quality to sustain destination competitiveness. Specific Background: Pijar Park Kudus, as a semi-artificial nature-based tourist destination, integrates tourist attractions, halal facilities, and visitor satisfaction to attract Muslim tourists. Knowledge Gap: Previous studies have rarely investigated the integration of tourist attractions, halal facilities, and visitor satisfaction within a single analytical model in local tourism contexts. Aims: This study aims to analyze the role of tourist attractions, halal facilities, and visitor satisfaction in shaping revisit intention. Results: Using a quantitative survey of 113 respondents, the findings reveal that tourist attractions, halal facilities, and visitor satisfaction each have positive and significant relationships with revisit intention, both partially and simultaneously, with a contribution of 77.3% to its variance. Novelty: This study highlights halal facilities as a key determinant within local tourism settings and integrates multiple variables in a unified model applied to a semi-artificial nature destination. Implications: The findings provide practical guidance for destination managers to develop integrated tourism strategies focused on improving attractions, halal facilities, and visitor satisfaction to strengthen visitor loyalty and support sustainable tourism development. HIGHLIGHTS • Tourist attractions contribute significantly to repeat visitation behavior• Halal-oriented services become a key determinant in local tourism context• Visitor satisfaction strengthens loyalty formation among young travelers KEYWORDS Tourist Attractions; Halal Facilities; Visitor Satisfaction; Revisit Intention; Halal Tourism